Refugees in Germany: Amongst Culture of Welcome and Xenophobia - Sophia Marek (International Journal of Interreligious and Intercultural Studies, 2019)
The refugee crisis in Germany is a part of the European migrant crisis in connection with the immigration of high numbers of people arriving in the European Union (EU) from across the Mediterranean Sea or overland through Southeast Europe. This period reached its’ summit in 2015/2016 with over a million protection seekers arriving in Germany.The high influx of protection seekers in such a short time has caused a social debate in Germany on how to handle the high numbers of immigrants and arrange the political asylum. There are different views on the reception of migrants that range from the culture of welcome to xenophobia. This can be observed in the society, where a part of the population gets involved with the refugees’ integration, whereas another (increasing) part foments anti-immigrant sentiments. Between those beliefs, many different attitudes and behaviors towards refugees can be found.This article discusses the situation of refugees and asylum seekers in Germany, concerning the divided opinions reaching from a culture of welcome to xenophobia. It addresses the transformation that Germany is currently undergoing and gives several examples of incidents of and against refugees that affect the mindset of the German population.